2019
DOI: 10.24920/003463
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Hidden Blood Loss During Posterior Spinal Surgery

Abstract: Objective Identification of the risk factors for extraordinary hidden blood loss (HBL) could clarify the underlying causes and provide more appropriate management. This study aims to identify the predictors of HBL in spinal surgery. Methods Medical records were retrospectively retrieved to collect the data of patients who undergoing posterior thoracic and lumbar fusion surgery or scoliosis surgery. Demographic information, perioperative visible blood loss volume, as well as laboratory results were recorded. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Up to now, the specific mechanisms and causes of HBL are not fully understood. The possible explanations are as follows: the trauma leads to the infiltration of blood into the interstitial space 8 ; the increased permeability of the cell membrane of some tissues in the trauma environment leads to hemolysis after the swelling and rupture [33][34][35] ; the increase in the fibrinolytic system during stress tissue plasminogen activator, which increases the potential for bleeding 36 . Especially for elderly patients with PLIF, the loose back muscle space provides a larger space for HBL, and the existence of an internal fixation system provides a potential space for HBL 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the specific mechanisms and causes of HBL are not fully understood. The possible explanations are as follows: the trauma leads to the infiltration of blood into the interstitial space 8 ; the increased permeability of the cell membrane of some tissues in the trauma environment leads to hemolysis after the swelling and rupture [33][34][35] ; the increase in the fibrinolytic system during stress tissue plasminogen activator, which increases the potential for bleeding 36 . Especially for elderly patients with PLIF, the loose back muscle space provides a larger space for HBL, and the existence of an internal fixation system provides a potential space for HBL 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [27][28][29][30] indicate that gender, multilevel, operative time, fibrinogen level, ASA classification, autologous and allogeneic transfusion, BMI, and surgical method were independent risk factors for HBL in posterior lumbar interbody fusion. Here, to investigate the effect of surgical method on HBL, we used other variables as control variables.…”
Section: Discussionmentioning
confidence: 96%
“…Bai 17 and Wen et al . 7 both concluded that patients above 60 years were at risk factor for HBL in orthopaedic surgery.…”
Section: Discussionmentioning
confidence: 96%